MO021GALECTIN 3 LEVEL IS REDUCED BY TREATMENT WITH SODIUM BICARBONATE IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (6th June 2020) - Dobre, Mirela; Patel, Neil; Sapa, Hima; Horwitz, Edward; Melamed, Michal; Hostetter, Thomas
Abstract: Background and Aims: Circulating cardiac biomarkers implicated in the pathogenesis of heart disease are a non-invasive platform to assess the cardiovascular disease (CVD) burden in individuals with chronic kidney disease (CKD). Galectin 3 is a 26 kDa β-galactoside-binding lectin that has a graded and positive association with CKD stages. In animal models, inhibition of galectin-3 prevents myocardial fibrosis. These pre-clinical findings have not been replicated in randomized controlled studies in humans. Metabolic acidosis of CKD has been shown to be associated with adverse CVD outcomes. We sought to examine whether correction of metabolic acidosis of CKD leads to lower circulating levels of Galectin 3, as an expression of myocardial fibrosis. Method: A total of 95 participants with stages 3 and 4 CKD and a serum bicarbonate level between 21-25 mEq/L, were randomized to receive sodium bicarbonate at a dose of 0.4 mEq/kg/day once a day or placebo for two years at two clinical sites in US. Galectin 3, was measured at study baseline and after one year. Results: Fifty participants were randomized to sodium bicarbonate and 45 to placebo. Mean age (SD) was 61.4 (10.2) years, 48% were women, 57% were non-Hispanic black, and 40% were non-Hispanic white, 61% had diabetes mellitus and 90% had hypertension at baseline. Mean baseline serum bicarbonate level was 23.5 (SD 1.7), mean (SD) baseline eGFR was 38.8 (11.2) ml/min/1.7m 2 and mean (SD) baseline systolic BP was 130 (17) mmHg. There were no differences in baseline characteristics between treatment groups. Compared to the placebo group, participants randomized to sodium bicarbonate had statistically significant change in the levels of Galectin 3 after one year of treatment (-7.12% vs 7.76% and -1.25 vs 1.54 ng/ml, p=0.03 in the sodium bicarbonate vs. placebo group, respectively, Figure). In subgroup analyses by CKD stages, participants with stage 3A randomized to sodium bicarbonate observed the highest decrement in Galectin 3 levels (-19.2% vs 14.7%, p=0.01; -3.3% vs -4.8%, p=0.49; and -7.4% vs 29.1%, p=0.09; for CKD 3B, 3B and 4, respectively). Conclusion: The level of Galectin 3 was reduced in patients with CKD 3 and 4 treated with sodium bicarbonate. This provides a framework for future therapeutic interventions aimed at reduction of myocardial fibrosis in patients with CKD and metabolic acidosis.